Computational modeling of degradation process of biodegradable magnesium biomaterials. (September 2021) - Barzegari, Mojtaba; Mei, Di; Lamaka, Sviatlana V.; Geris, Liesbet
Highlights: Mathematical modeling of corrosion of degradable magnesium. Bayesian optimization for model calibration using experimental data. Dedicated corrosion tests in saline and SBF solutions for validation. A good agreement of model predictions with experimentally obtained values. Mathematical presentation of local and global pH changes. Abstract: Despite the advantages of using biodegradable metals in implant design, their uncontrolled degradation and release remain a challenge in practical applications. A validated computational model of the degradation process can facilitate tuning implant biodegradation properties. In this study, a mathematical model of the chemistry of magnesium biodegradation was developed and implemented in a 3D computational model. The parameters were calibrated by Bayesian optimization using dedicated experimental data. The model was validated by comparing the predicted and experimentally obtained pH change in saline and buffered solutions, showing maximum 5% of difference, demonstrating the model's validity to be used for practical cases.